Sauvegarder le patrimoine, sauvegarder l’individu. Un regard sur la politique patrimoniale de l’immatériel au Brésil - Elaine Brito; Nolwenn Pianezza (In Situ)
This article takes a look at the way the idea of heritage safeguarding is understood in Brasil, viewed from the point of view of intangible heritage policies in this country. Our diachronic analysis of the concept allows us to indentify several characteristics of the way the intangible heritage is managed in Brasil, and how social actors canrelate to these management procedures. We look in particular at the way different actors can use Brasilian heritage policies and how these actors can mobilise intangible heritage procedures in order to constitute themselves as legitimate partners in public life, and pursue their own socio-political aims.